The application of tie-down gillnet to improve the capture of blackfin flounder (Glyptocephalus stelleri) in a sustainable way - Kim, Seonghun; Kim, Hyungseok; Kim, Pyungkwan (Frontiers in Marine Science, 2023)
In this study, experimental fishing trials were performed to quantitatively evaluate and compare the fishing performance of trammel nets, tie-down gillnets, and single gillnets used for catching blackfin flounder. A total of eight cruises performed at depths of 100–140 m in the waters near Yangyang, Gangwon-do, Korea. Fisheries laws in Korea currently restrict the use of trammel nets due to concerns about overfishing and bycatch. Tie-down gillnets have a support line that changes their stretched height, thus increasing their catch rate, and are an attractive alternative to trammel nets or single gillnets; unmodified gillnet. Due to a lack of quantitative evaluation of their fishing performance, the performances of these three types of gillnets quantitatively compared. The number and weight of fish, particularly blackfish flounder, caught by each net under similar circumstances were compared. Our results suggest that the fishing performance of trammel nets and tie-down gillnets is much higher than that of single gillnets. Compared to single gillnets, trammel nets performed better by 2.98 times and 2.45 times, in terms of the total number and weight of fish caught, respectively, and tie-down gillnets performed better by 2.09 times and 1.97 times, respectively. In addition, the bycatch rate of tie-down gillnet for immature blackfin flounder with the total length less than 20 centimeters was similar to single gillnet ; single gillnet 17.5% of immature blackfin flounder, tie-down 20% of immature blackfin flounder, trammel net 62.5% of immature blackfin flounder. Given that many flat fish such as flounders fall out of the net during the fishing process after being stuck in single gillnets, fishermen hope to use trammel nets. However, the relatively high catch rate of trammel nets likely necessitates restrictions for their use. This study suggests that tie-down gillnets are an option for sustainable fishing practice given that they perform better than single gillnet and reduce bycatch of immature blackfin flounder when compared to trammel nets.